Strength and serviceability of damaged and repaired concrete structures - Tan, Chek Hui. (2009)
Durability of concrete structures is of great concern at present not only to engineers but to members of the public who use public and office building and own apartments and demand assurances that the buildings are not likely to deteriorate or collapse.